ANALISIS KINERJA LINGKUNGAN DAN MEKANISME GCG TERHADAP PENGUNGKAPAN PERTANGGUNGJAWABAN SOSIAL - Puji Handayati (Jurnal Akuntansi Aktual, 2017)
This study aims to test the influence of environmental performance valued based on PROPER toward disclosure of social responsibility. Good environment performance will increase Corporate Social Responsibility (CSR). Meanwhile, the implementation of Good Corporate Governance (GCG) proxied by institutional ownership, board of director, independence board of director, auditor committee will increase the disclosure of GCG. In this study, the CSR disclosures were indicated by Global Reporting Initiative (GRI). The design of this study was causal assosiative. The population consists of 154 manufactur firms listed in Indonesian Stock Exchange of period 2012 – 2014. Under the purposively sampling technique, the number of the sample obtained was 11 firms. The hyphotheses were tested using multiple regression. The findings of this result showed that environmental performance and auditor committee influenced the CSR disclosures. On the other hand, institutional ownership and the board of director did not influence the CSR disclosures. The findings also indicated that the higher the environment performance, the better the quality of CSR disclosure.Keywords: environmental performance, GCG mechanism, social responsibility disclosure